Control interno y la gestión de inventarios en la empresa Telecable Iquitos SAC, periodo 2022 - Sullon Amaringo, Dayana Josetty (2023)
The present research work had the general objective of determining the relationship between internal control and inventory management in the company Telecable Iquitos SAC, period 2022, quantitative research, with a cross-correlational design type and non-experimental design; had 76 workers as study population, and a record of control reports made in the company Telecable Iquitos SAC, period 2022, the investigation concluded that according to the field of study there is a very high correlation between the internal control variable and Inventory management , given that according to the results the degree of correlation is in the range of 0.80-0.99 (very high correlation) being a very significant correlation since the value of Sig. (bilateral) is 0.01; Therefore, it can be affirmed that it has a 99% confidence level, so the general hypothesis is accepted, in addition to recommending that the company periodically disseminate internal control activities, in order to keep everyone involved in the organization informed. on the measures implemented to guarantee the integrity, reliability and compliance of the operations, so the periodic dissemination of internal control activities is not only a communication tool, but also a way to strengthen trust in the organization and maintain a high level of transparency in all operations.